Fabrication of ordered arrays of CNT/TiO2 nanotubes and their photocatalytic properties. Issue 27 (23rd February 2015) - Qu, Xiaofei; Cao, Lixin; Du, Fanglin
Abstract : In this work, fabrication and characterization of ordered arrays of CNT/TiO2 nanotubes imbedded in porous anodic aluminum oxide (AAO) membranes were reported. Abstract : In this work, fabrication and characterization of ordered arrays of CNT/TiO2 nanotubes imbedded in porous anodic aluminum oxide (AAO) membranes were reported. The coaxial core–shell structures were exploited for the photocatalytic degradation of organic pollutants, such as methyl orange. The presence of the CNT greatly enhanced the efficiency of photocatalytic activity compared with the bare TiO2 nanotubes. The key achievement of this work is to fabricate ordered arrays of CNT/TiO2 composite nanotubes with coaxial core–shell structures by using a simple, convenient, and environmentally friendly process. Further application of this CNT/TiO2 hybrid material in many fields could be hopefully expected.